From awareness to action: rethinking high school civic education for the digital generation in Indonesia - Andi Aco Agus; Andi Rizal; Muhajir Muhajir; Ahmad Jamalong (Cogent Education)
In Indonesia, Civic Education is taught through the subject Pendidikan Pancasila dan Kewarganegaraan (PPKn), which promotes civic responsibility grounded in national ideology. As civic life increasingly shifts to digital spaces, digital citizenship has become essential for youth. However, its integration into formal education remains limited. This study investigates how digital citizenship is understood and implemented in Indonesian high schools by examining students’ digital civic literacy and teachers’ strategies. Using a convergent mixed-methods design, it involved 120 students and 15 PPKn teachers from five senior high schools in Makassar, South Sulawesi. Results show that while students exhibit strong ethical awareness—particularly around online safety and misinformation—their civic engagement online remains passive. Teachers apply critical media literacy approaches but face barriers such as lack of training, rigid curriculum demands, and minimal institutional support. The findings highlight the intersection of national identity, digital engagement, and evolving educational policy, emphasizing the urgent need to embed digital citizenship into the PPKn curriculum. This requires sustained professional development and culturally responsive school-wide initiatives. Despite limitations such as urban focus and reliance on self-reports, the study calls for broader research to inform a more inclusive national framework for digital citizenship education.